DEVELOPING NEW BUSINESS MODEL FOR BOOK PUBLISHING COMPANY IN THE DIGITAL AGE: A CASE STUDY OF DUTA MEDIA TAMA - Sucipta, Dimas; Larso, Dwi (The Indonesian Journal of Business Administration, 2016)
Abstract. Creative economy is a growing industry but publishing industry as a part of creative economy faces more problems. Current data based on Indonesia book retailer company shows that total sales growth only 2% per year in 2015, that is lower than several years ago. At this time, company faces new business environment that is a digital era. The issues that company face are how to survive and growth in this digital era. Â The purpose of this research is to develop new business model for company which more relevant with digital age. For do that, it is necessary to has deeper understanding about the business situation which company face. The research method and framework is used in this research there are PEST Method, Porterâ??s Five Force, Market Research for customers analysis, internal analysis, and SWOT analysis. The survey method is used in market research with questionnaires to targeted market segment specifically who life in Bandung.Â The research result shows that in macro environment factors, the political and economy factor are tend to be positive for company future growth, but several changing external factors have an impact to company that are the growing of digital technology which influence customers behavior and trend of new culture. In microenvironment the force which has an impact to lowering company growth is substitute product that is free information or content in the internet while the digital book does not influence. In customers analysis shows that many customers have high reading interest to physical book, but their purchasing power is low, therefore they tend to choose internet for search free information although internet information still has a lot of weakness such as credibility of information and too much information. From that several analysis, the root cause of company slow growth is because of threat factor from internet free information that cause customers choose internet than physical books. The new business model is developed to face that new business environment, while the method is used business model generation. The result are seven business model ideas for this issue which after evaluating each others, the Digital Novel business model is a best business model solution for company. It is because from the research it is known that many customers like reading a physical book than digital book, fiction/novel book is the best selling and most favorite category, and customers always depend to digital technology as a modern lifestyle.Â Key words: business model, digital age, book publishingÂ